2014
DOI: 10.1371/journal.pone.0096684
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Accuracy and Feasibility of a Refractive Error Screening Program Conducted by School Teachers in Pre-Primary and Primary Schools in Thailand

Abstract: IntroductionAs part of the development of a system for the screening of refractive error in Thai children, this study describes the accuracy and feasibility of establishing a program conducted by teachers.ObjectiveTo assess the accuracy and feasibility of screening by teachers.MethodsA cross-sectional descriptive and analytical study was conducted in 17 schools in four provinces representing four geographic regions in Thailand. A two-staged cluster sampling was employed to compare the detection rate of refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 17 publications
4
36
1
Order By: Relevance
“… 19 – 66 Identified articles were from 13 countries spanning five World Health Organization (WHO) Regions including Africa (eight studies), the Americas (10 studies), the Eastern Mediterranean (one study), South-East Asia (18 studies) and the Western Pacific (11 studies). Identified articles comprised 19 school-based eye-care programme evaluations, 19 – 33 , 62 – 64 , 66 16 studies investigating spectacle compliance associations, 34 48 , 65 eight studies exploring the quality of various eye-care screening personnel, 49 56 four studies evaluating the effectiveness of eye health promotion, 57 60 and one study that included both spectacle compliance and the quality of screening personnel 61 . When appraised for quality, 15 we classified 18 studies as being of high quality, 20 as medium quality and 10 as low quality.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 19 – 66 Identified articles were from 13 countries spanning five World Health Organization (WHO) Regions including Africa (eight studies), the Americas (10 studies), the Eastern Mediterranean (one study), South-East Asia (18 studies) and the Western Pacific (11 studies). Identified articles comprised 19 school-based eye-care programme evaluations, 19 – 33 , 62 – 64 , 66 16 studies investigating spectacle compliance associations, 34 48 , 65 eight studies exploring the quality of various eye-care screening personnel, 49 56 four studies evaluating the effectiveness of eye health promotion, 57 60 and one study that included both spectacle compliance and the quality of screening personnel 61 . When appraised for quality, 15 we classified 18 studies as being of high quality, 20 as medium quality and 10 as low quality.…”
Section: Resultsmentioning
confidence: 99%
“…As the availability of eye-care specialists can be limited in school settings, particularly in low- and middle-income countries, studies have investigated the use of teachers, nurses, certified medical assistants and key informants for the provision of screening and basic eye-care for children 20 , 21 , 29 , 51 54 , 56 , 58 , 60 , 62 . Several studies found that training teachers in vision screening enabled the provision of a good-quality 51 , 53 , 56 and cost–effective service, 53 while facilitating the opportunity to motivate spectacle use among students 54 . Two studies reported that the use of teachers as vision screeners did not create significant burdens on normal workloads, and in fact enhanced rapport with children and parents 50 , 56 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations